Correlation of Serum Vitamin D3 level with Severity of Liver Dysfunction in Cirrhotic Patients - Mazumder, Nihar Ranjan; Paul, Anjan Kumar; Uddin, Dalil; Abedin, Forhad; Mojumder, Hasan Iqbal; Akter, Sabina; Hassan, Nazmoul (Journal of Comilla Medical College Teachers' Association, 2025)
Background: Vitamin D3 is a steroid hormone, which is mostly known as a regulator of calcium and bone metabolism. It has a significant role in the natural history of chronic liver diseases, such as chronic hepatitis C and non-alcoholic fatty liver disease (NAFLD). The deranged metabolism of vitamin D3 in liver cirrhosis was mainly attributed to impaired 25(OH)-vitamin D3 hydroxylation of the precursor vitamin D3 due to insufficient liver function. This study focused on the association of hepatic insufficiency with bone demineralization, osteomalacia, osteoporosis and minerals metabolism. Objective: To find out the correlation of serum Vitamin D3 level with severity of liver dysfunction in cirrhotic patients. Methods: A six-month Cross sectional study carried out at the department of Hepatology and Medicine, Comilla Medical College. Ethical approval from the institutional review board was obtained to ensure patient privacy and confidentiality. Results: Among 50 patients where male was 38(76%) and female was 12(24%) male to female ratio was 3.16:1. Age group distribution revealed most patients were affected at middle age groups 31-40 years 12(24%) and 41-50 years 15(30%). From the age distribution of the patients, it was found that highest number of patients was in the age group of 41-50 years. Correlation of Child Pugh grading with vitamin D3 level revealed in CP A had mean vitamin D3 was 27.50, in CP B had 27.36 and in CP C had 21.42. The results showed that a significant relationship was observed between Child Pugh classification and different vitamin D3 levels; on that basis, there was a trend of lower vitamin D3 level with cirrhosis increase severity. Conclusion: In conclusion there is a strong trend towards vitamin-D3 levels predicting severity in patients with cirrhosis and a low value seems to identify patients at higher risk for more severity. Correlation of vitamin D3 level and CLD severity is found statistically significant, the clinical implication of vitamin D3 therapy in chronic liver disease may make a therapeutic benefit to the patient. J Com Med Col Teachers’ Asso July 2025; 29(2):114-118